2020
DOI: 10.1186/s40644-020-00333-y
|View full text |Cite
|
Sign up to set email alerts
|

Does whole-body bone SPECT/CT provide additional diagnostic information over [18F]-FCH PET/CT for the detection of bone metastases in the setting of prostate cancer biochemical recurrence?

Abstract: Background: To assess whether whole-body (WB) bone SPECT/CT provides additional diagnostic information over [18F]-FCH PET/CT for the detection of bone metastases in the setting of prostate cancer biochemical recurrence (PC-BR). Methods: Patients referred for a PC-BR and whom benefited from a WB bone SPECT/CT and FCH PET/CT were retrospectively included. Tests were classified as positive, equivocal, or negative for bone metastases. A best valuable comparator (BVC) strategy including imaging and follow-up data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The two groups concluded that performing [ 68 Ga]-PSMA PET-CT significantly increased the diagnostic accuracy compared to bone SPECT-CT. Regarding 18 Fluorine ([ 18 F])-Choline, a study that included 115 prostate cancer patients, performed in 2020 by Leiris et al [ 29 ], investigated whether bone SPECT-CT provides additional diagnostic information over [ 18 F]-Choline PET-CT for detecting bone metastases in the setting of prostate cancer biochemical recurrence. The authors concluded that bone SPECT-CT does not provide additional diagnostic information over [ 18 F]-Choline PET-CT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two groups concluded that performing [ 68 Ga]-PSMA PET-CT significantly increased the diagnostic accuracy compared to bone SPECT-CT. Regarding 18 Fluorine ([ 18 F])-Choline, a study that included 115 prostate cancer patients, performed in 2020 by Leiris et al [ 29 ], investigated whether bone SPECT-CT provides additional diagnostic information over [ 18 F]-Choline PET-CT for detecting bone metastases in the setting of prostate cancer biochemical recurrence. The authors concluded that bone SPECT-CT does not provide additional diagnostic information over [ 18 F]-Choline PET-CT.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing bone SPECT-CT diagnostic accuracy to [ 68 Ga-PSMA] or [ 18 F]-Choline, used in prostate cancer patient management (Janssen et al [ 23 ], Dyrberg et al [ 28 ], Leiris et al [ 29 ] and Simsek et al [ 30 ]), the results indicated that the AUC, sensitivity, and specificity of bone SPECT-CT ranged between 0.82 and 0.89, 82 and 100% and 82 and 94%, compared to 0.82 and 1.00, 93 and 100% and 95 and 100%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation